2015
DOI: 10.1016/j.juro.2015.02.1807
|View full text |Cite
|
Sign up to set email alerts
|

Mp89-08 Underactive Bladder Is Not a Symptom Complex

Abstract: INTRODUCTION AND OBJECTIVES: We herein attempt to define which frequency-volume chart (FVC) parameters improve when nocturia improves.METHODS: A retrospective analysis of 24-hour FVCs was performed. Nocturnal urine volume (NUV, urine produced from time of retiring through first void upon arising), nocturia index (Ni, [NUV]/ maximum voided volume [MVV]), nocturnal polyuria index (NPi, [NUV]/ 24 hour volume), nocturnal bladder capacity index (NBCi, actual number of nocturnal voids [ANV]epredicted number of night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other studies go to the extremes, where they address that patients with DU will benefit from prostate surgical procedures even when they are not associated with BOO [32] . Finally, in a retrospective analysis of 4272 UDS, it was concluded that underactive bladder is not a symptom complex and DU should be based on UDS diagnosis [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies go to the extremes, where they address that patients with DU will benefit from prostate surgical procedures even when they are not associated with BOO [32] . Finally, in a retrospective analysis of 4272 UDS, it was concluded that underactive bladder is not a symptom complex and DU should be based on UDS diagnosis [33] .…”
Section: Resultsmentioning
confidence: 99%